Management of intractable epistaxis in patients who received radiation therapy for nasopharyngeal carcinoma - He, Cheng-Cheng (Springer Berlin Heidelberg, 2013)
To report clinical manifestations, bleeding point localization, and outcomes of management in 16 patients with 16 instances of intractable epistaxis after radiation therapy for nasopharyngeal carcinoma. Retrospective chart review of 16 patients with nasopharyngeal carcinoma (mean age 52.06 ± 14.37 years) with 16 instances of intractable epistaxis during the past 5 years, whose diagnosis was confirmed by angiography (n = 10) or MRI/CT imaging studies and clinical manifestations (n = 6). The mean radiation dose to the affected carotid artery was 101.37 ± 34.85 Gy. Bleeding points were detected in the internal carotid artery (n = 8) or external carotid artery (n = 8). Detachable balloons were used in one affected artery for vascular occlusion; six were treated using an absorbable gelatin sponge (n = 4) or microcoils (diameter 1 mm) (n = 2). Endovascular embolization was successful in seven radiation carotid blowout syndromes with cessation of hemorrhage. One patient underwent external carotid artery ligation and one patient recovered without treatment. The clinical follow-up was 3 months. Therapeutic endovascular embolization of intractable epistaxis is both efficient and safe. It should be considered as the primary treatment modality in intractable epistaxis of nasopharyngeal carcinoma.